Association of Differing Qatari Genotypes with Vitamin D Metabolites - Youssra Dakroury; Alexandra E. Butler; Soha R. Dargham; Aishah Latif; Amal Robay; Ronald G. Crystal; Stephen L. Atkin (International Journal of Endocrinology)
Objective. Genetic studies have identified four Qatari genotypes: Q1 Arab, Bedouin; Q2 Asian/Persian; Q3 African; and a fourth admixed group not fitting into the previous 3 groups. This study was undertaken to determine if there was an increased risk of deficiency of vitamin D and its metabolites associated with differing genotypes, perhaps due to genetic differences in skin pigmentation. Methods. 398 Qatari subjects (220 type 2 diabetes and 178 controls) had their genotype determined by Affymetrix 500 k SNP arrays. Total values of 1,25-dihydroxyvitamin D (1,25(OH)2D), 25-hydroxyvitamin D (25(OH)D), 24,25-dihydroxyvitamin D (24,25(OH)2D), and 25-hydroxy-3epi-vitamin D (3epi-25(OH)D) concentrations were measured by the LC-MS/MS analysis. Results. The distribution was as follows: 164 (41.2%) genotyped Q1, 149 (37.4%) genotyped Q2, 31 (7.8%) genotyped Q3, and 54 (13.6%) genotyped “admixed.” Median levels of 25(OH)D and 3epi-25(OH)D did not differ across Q1, Q2, Q3, and “admixed” genotypes, respectively. 1,25(OH)2D levels were lower (p<0.04) between Q2 and the admixed groups, and 24,25(OH)2D levels were lower (p<0.05) between Q1 and the admixed groups. Vitamin D metabolite levels were lower in females for 25(OH)D, 1,25(OH)2D (p<0.001), and 24,25(OH)2D (p<0.006), but 3epi-25(OH)D did not differ (p<0.26). Diabetes prevalence was not different between genotypes. Total 1,25(OH)2D (p<0.001), total 24,25(OH)2D (p<0.001), and total 3epi-25(OH)D (p<0.005) were all significantly lower in diabetes patients compared to controls whilst the total 25(OH)D was higher in diabetes than controls (p<0.001). Conclusion. Whilst 25(OH)D levels did not differ between genotype groups, 1,25(OH)2D and 24,25(OH)2D were lower in the admixed group, suggesting that there are genetic differences in vitamin D metabolism that may be of importance in a population that may allow a more targeted approach to vitamin D replacement. This may be of specific importance in vitamin D replacement strategies with the Q2 genotype requiring less, and the other genotypes requiring more to increase 1,25(OH)2D. Whilst overall the group was vitamin D deficient, total 25(OH)D was higher in diabetes, but 1,25(OH)2D, 24,25(OH)2D, and 3epi-25(OH)D were lower in diabetes that did not affect the relationship to genotype.